Mathematical sequences behind genetic codes - Goh, Alfred Yuhui (Nanyang Technological University, 2019)
Genetics is an ever-developing concept. The realm of Mathematics and Science have always been that of discovery, renewal and reconciliation. Something determined to be factual in a moment could have its status quo overturned in a matter of years, months, days or even hours. Back in the 1980s, it was thought that genetic materials lack adaptability. Since then, tens of hundreds of other research have proved otherwise. There was never a hard and fast rule dictating the ways of Mathematics and Science. Staying true to the previous statement, this paper aims to propose the union between genetic codes and mathematical sequences in hopes of uncovering a method to further understanding of and predict novel genetic codes. Through analyzing number sequences, this paper attempts to draw links between existing laws of mathematics to genetic codes. The results of this paper could contribute to relevant works and urge the invention of computational methodology in order to help assess larger sample size in the future.